Findings from interview series and qualitative validation of webmetric analysis - Fry, J; Schroeder, R; Virkar, S (Oxford Internet Institute, 2006)
In order to help determine whether the winner-take-all hypothesis applied to patterns of access to information we conducted a series of semi-structured interviews in a sub-sample of the original six global domains. These were Terrorism, HIV/AIDS, Climate Change, and Internet and Society. In total twenty UKbased active researchers were interviewed; five from each of the four domains. Interviewees were asked about their research background, key institutions, groups and people in their research networks, and the variety of online resources they used. Questions also focused on their online search strategies, such as the tools they used for finding information, the keywords they used and what kind of entities they tended to search for e.g. people, groups or institutions.